KESIAPAN BANGSA INDONESIA MENGHADAPI PERKEMBANGAN ERA INDUSTRI 4.0 DILIHAT DARI SUDUT PANDANG TUJUAN DAN CITA – CITA BANGSA INDONESIA - Muchammad Hifni; Ahmad Nur Ahsan (JURNAL MAHATVAVIRYA, 2022)
This study describes digital developments in the industrial era 4.0 where all electronic devices will increasingly penetrate the world, digitizing all kinds of objects that are needed daily will be attached to the current era. The conditions of the Industry 4.0 era have given birth to a variety of advanced technologies, such as artificial intelligence (AI), Internet of Things (IoT), wearable technology, advanced robotics, and 3D printing. Generally, these advanced technologies use cloud computing (Data Cloud) as a data storage medium in the form of a computer server that is reached through access to the internet. The technology used in industry 4.0 makes everything connected virtually via the internet. The role of information technology can no longer be dammed so that there is a social impact for a new generation in the state, technological sophistication, the fourth industrial revolution will have a profound impact on the basic character of relations between countries and national security. The danger that threatens a hyper-connected world is increasing instability and inequality which may lead to increased fragmentation of segregation and social unrest that will eventually create conditions that fuel violent extremism. The readiness of human resources and strong infrastructure is an absolute requirement that results are carried out to keep up with the development of the industrial era 4.0